Use of Simultaneous Nasogastric and Nasojejunal Tubes for Proximal Intestinal Atresias - A Preliminary Report - Mahajan, Jai Kumar; Yhoshu, Enono (Journal of Neonatal Surgery, 2017)
Please see fulltext.